2012
DOI: 10.1515/iral-2012-0008
|View full text |Cite
|
Sign up to set email alerts
|

The comparative effects of processing instruction and dictogloss on the acquisition of the English passive by speakers of Turkish

Abstract: The current study presents the results of an experiment investigating the effects of processing instruction (PI) and dictogloss (DG) on the acquisition of the English passive voice. Sixty speakers of Turkish studying English at university level were assigned to three groups: one receiving PI, the other receiving DG and the third serving as a control group. Assessment measurements consisted of an interpretation task, a sentence-level production task and a reconstruction task in a pretest-posttest design. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 11 publications
(15 reference statements)
3
20
0
Order By: Relevance
“…Processing instruction is only useful in so far as it deliberately structures input to steer learners away from the lessthanoptimal processing strategies while also considering any corollaries that affect these strategies. As I have noted elsewhere, a number of studies have gone awry in attempting to research PI because the researchers failed to (completely) consider the principles and their corollaries in the con struction of appropriate intervention activities (e.g., Sanz & VanPatten, 1998;Uludag & VanPatten, 2012; see also Wong, 2004).…”
Section: The Nature Of Input Processingmentioning
confidence: 99%
“…Processing instruction is only useful in so far as it deliberately structures input to steer learners away from the lessthanoptimal processing strategies while also considering any corollaries that affect these strategies. As I have noted elsewhere, a number of studies have gone awry in attempting to research PI because the researchers failed to (completely) consider the principles and their corollaries in the con struction of appropriate intervention activities (e.g., Sanz & VanPatten, 1998;Uludag & VanPatten, 2012; see also Wong, 2004).…”
Section: The Nature Of Input Processingmentioning
confidence: 99%
“…These are meaning-based output instruction (e.g., Benati 2005;Farley 2001a), input-based interventions (e.g., Marsden 2006), dictogloss (Uludag & VanPatten 2012;) and communicative output tasks (Toth 2006). All these studies address the fundamental question of the effectiveness of processing instruction as a type of intervention and take VanPatten and Cadierno (1993) and Cadierno (1995) as their point of departure.…”
Section: Milestone: Pi Is Effective Instructionmentioning
confidence: 99%
“…The effects of processing instruction have been compared with the effects of meaning-based output instruction in other studies (Lee & Benati, 2007a;Morgan-Short & Bowden, 2006), and with other interventions such as dictogloss (Uludag & VanPatten, 2012;VanPatten et al, 2009). The results of these studies confirmed the effectiveness of processing instruction in improving learners' performance on both interpretation and production sentence-level tests.…”
Section: Studies Measuring the Effects Of Processing Instruction Versmentioning
confidence: 99%